Metastatic Eye Cancer as a Prognostic Factor for Patient Survival - review of literature - Ristić, Milana; Cekic, Sonja; Zlatanović, Nevena (Acta medicae Medianae, 2021)
The eye is a rare organ of metastatic disease spreading. Secondary eye tumors can be diagnosed in all structures of the eye from ocular adnexa to uvea, and optic disc.Metastatic eye tumors originate from different primary tumor lesions such as melanoma, squamous cellular carcinoma, lymphoid tissue tumors, breast, lungs, gastrointestinal tract, prostate, kidney, bladder.  Some of these primary tumors are specific to the place of metastatic lesions. Symptoms and clinical manifestation varying according to the involvement of different structures. Diagnosis of metastatic eye tumor is connected to the poor prognosis. Treatment depends on primary tumor lesions, part of the eye that is involved, stage of the disease. Novel immunological, biological, and radiotherapy techniques give promising results in treatment.
Keywords: metastatic cancer, eye, prognosis, treatment